Vitamin E supplementation and secondary metabolites interactions and effects on melanoma growth - Ottino, Paulo (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1997)
The present study was undertaken to determine the effects and possible mechanism of action of vitamin E succinate on malignant murine melanoma (BL6) and non-malignant monkey kidney (LLCMK) cell growth in vitro. Studies revealed that supplementation of 5, 7 and lOJLg/ml vitamin E succinate significantly inhibited BL6 cell growth, while in LLCMK cells no significant increase or decrease in growth was observed. The actual mechanism by which vitamin E succinate inhibits BL6 cell growth is at present unclear. Studies have suggested a radical or oxidant involvement in a number of degenerative diseases such as cancer, and that supplementation of antioxidant vitamins such as vitamin E may function to reduce cancer cell growth by quenching free radical species and preventing lipid peroxidation. In addition to its antioxidant role in a cell, vitamin E is believed to modulate the activities of various enzymes and metabolites in the eicosanoid pathway. Hence, this study investigated the effects of vitamin E succinate supplementation on free radical and lipid peroxidation levels, as well as the activities of various enzymes and metabolites ill the eicosanoid pathway. Throughout this study, emphasis was placed on BL6 melanoma cells since the magnitude of the relationship between LLCMK growth and the levels of various enzymes and metabolites in the eicosanoid pathway varied considerably from one experiment to another and did not show the consistent trend found with the BL6 cells. A decrease in cell growth was found to be accompanied by a concomitant increase rather than a decrease in the levels of free radicals and lipid peroxidation, suggesting that the growth inhibitory effects of vitamin E succinate on BL6 cells in vitro was not due to its antioxidant properties associated with the vitamin E component, but rather due to one or more of its other potential roles within the cell. This proposal was further strengthened by findings that vitamin E succinate, a non-physiological antioxidant in its esterified form, did not undergo significant cleavage to free vitamin E in the BL6 cells. Vitamin E succinate is believed to modulate membrane bound enzyme activities through physicochemical interactions with membrane lipids and changes in membrane fluidity. Hence, this study investigated the role of vitamin E succinate in modulating the activity of various enzymes and secondary messengers in the eicosanoid pathway. Supplementation of l-lOjLg/ml vitamin E succinate resulted in an overall increase in phospholipase A2 activity while cyclooxygenase and adenyl ate cyclase activities were found to be significantly increased at vitamin E succinate concentrations of 7 and WjLg/ml respectively. A significant increase in" 5-LOX activity was observed a! 10jLg/mi supplementation. The suggestion that vitamin E succinate modulates membrane bound enzyme activities was further strengthened by uptake and cellular distribution studies, which showed significantly higher levels of vitamin E succinate in membrane fractions of BL6 cells when compared with stroma fractions. Another factor which could account for elevated PLA2,-5-LOX and COX activities in BL6 cells as a result of vitamin E succinate supplementation, was that of intracellular calcium levels. Supplementation of BL6 cells with 1-7 jLg/ml vitamin E succinate resulted in an overall increase in intracellular calcium levels. These changes in calcium levels however were positively correlated with changes in PLA2 activity only. Since the rate of prostaglandin synthesis is controlled by phospholipase A2 activity, and net prostagiandin production is dependant on cyclooxygenase activity, the effects of vitamin E succinate supplementation on prostaglandin levels in BL6 cells was determined. Vitamin E succinate supplementation resulted in a significant decrease in prostaglandin D2 levels at vitamin E succinate concentrations of 3, 5, 7 and lOjLg/ml respectively, while prostaglandin F2a levels were significantly decreased at 1-10jLg/ml vitamin E succinate. The increases in prostaglandin E2 and 12 levels were inversely related to BL6 cell growth suggesting that both prostaglandins may act as negative regulators of BL6 cell growth. When comparing prostaglandin E2 levels to prostaglandin 12 levels in BL6 cells, significantly higher levels of prostaglandin E2 were found, suggesting that vitamin E succinate effects were mediated primarily through an increase in prostaglandin E2 levels. Furthermore, prostaglandin E2 levels are believed to modulate adenylate cyclase activity. It is therefore reasonable to conclude that the increased adenyl ate cyclase activity found in BL6 cells was dependant on prostaglandin E2 levels, since increases in prostaglandin E2 levels at 7 and lOjLg/ml vitamin E succinate correlated with an increase in adenylate cyclase activity and cyclic adenosine monophosphate levels. Thus it appeared that the observed inhibitory effects of vitamin E succinate supplementation on BL6 cell growth was not due to the antioxidant properties associated with the vitamin E component of the vitamin E succinate molecule, but was rather mediated in part through a cascade effect initiated by phospholipase A2 activation and archidonic acid release. This initial effect then appeared to result in an increase in cyclooxygenase activity and activation of a prostaglandin E2-adenylate cyclase-cyclic adenosine monophosphate linked system, ultimately altering cyclic adenosine monophosphate levels and inhibiting BL6 cell growth. This was confirmed when BL6 cells were supplemented with indomethacin, a cyclooxygenase inhibitor. Supplementation with the inhibitor resulted in vitamin E succinate having no inhibitory effects on BL6 cell growth. Furthermore, when comparing the levels of prostaglandin ~, adenylate cyclase activity and cyclIC adenosine monophosphate in the indomethacin treated cultures to non-indomethacin treated cultures, markedly lower levels of these metabolites were found in the indomethacin treated cultures. The cause of the increase in free radical and lipid peroxidation levels in BL6 cells following vitamin E succinate supplementation was further investigated. Cyclooxygenase enzymes are believed to generate free radical species and contribute to lipid peroxidation levels during catalytic activity. Markedly lower levels of free radicals and lipid peroxidation in indomethacin treated cultures were found when compared with vitamin E succinate treated cultures alone, suggesting that the increases in free radical and lipid peroxidation levels in BL6 cells supplemented with vitamin E succinate were indirectly due to an increase in cyclooxygenase activity in these cells.
Keywords: Vitamin E; Melanoma